EVALUATION OF IMPLEMENTATION OF COMPREHENSIVE EMERGENCY NEONATAL OBSTETRICS SERVICES PROGRAM (PONEK) - Irma Irma; Erni Gustina (Universitas Ahmad Dahlan, 2018)
Background: Contributing factors to maternal and infant mortality rates are caused by delays in decision making, late referral and late handling at health facilities or referral sites. One of the efforts to reduce maternal, infant and under-five mortality rates is the provision of comprehensive emergency neonatal obstetric service facilities (PONEK= Program Pelayanan Obstetri Neonatal Emergensi Komprehensif) in hospitals. The key to the success of PONEK is the availability of appropriate healthcare personnel competence, infrastructure, facilities and reliable management. Objective: Evaluate the PONEK program at General Hospital PKU Muhammadiyah Yogyakarta City (RSU PKU Muhammadiyah Yogyakarta City) Methodology: This research used qualitative approach, case study designed at RSU PKU Muhammadiyah Yogyakarta in September 2017. The subjects were 5 employees of PONEK Team and 3 patients, and using Purposive Sampling technique. Data collection by in-depth interviews and observations. Data analysis consisted of the stages of data reduction, data presentation, drawing conclusions and source triangulation. Result: Input program of PONEK in RSU PKU Yogyakarta is good in terms of quantity of good availability of human resources, funds, and infrastructure facilities. The process of planning, organizing and supervision is good, while in the implementation process has not run well, because one of the activities that support the PONEK of education and training has not been 100% running. Output of PONEK that has not been achieved such as training that cannot be implemented in accordance with a predetermined schedule. The service quality of the PONEK program in terms of patients is quite good and satisfied with the services provided. Conclusion: The implementation of comprehensive emergency neonatal obstetric service program in PKU Muhammadiyah General Hospital as a whole has been going well even though it is not perfect, because there are some parts that are carried out optimally.